1989
DOI: 10.1016/0304-3940(89)90414-x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine, ‘pertussis-sensitive’ G-proteins, and K+ conductance in central mammalian neurones under energy deprivation

Abstract: There is a striking similarity between the effects of adenosine and of hypoxia or glucose depletion on membrane potential and conductance of hippocampal neurones in tissue slices of rat brain. Both induce a membrane hyperpolarization by an increase in potassium conductance. It seemed likely, therefore, that a rise in extracellular adenosine concentration during energy deprivation may link neuronal metabolism with membrane K ÷ conductance. To test this hypothesis, we have now investigated the effects of hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…This suggests that cell hyperpolarization during hypoxia is not the result of G-protein-linked adenosine A1 receptors opening K+ channels. These results are in agreement with the studies of Leblond & Krnjevic (1989) who found that caffeine, a weak, non-selective adenosine antagonist (Bruns et al, 1986) did not attenuate hypoxia-induced hyperpolarization and Spuler & Grafe (1989) who found that pertussis toxin treatment (which abolished the hyperpolarization induced by application of exogenous adenosine) did not block the hyperpolarization during anoxia. The fall in evoked field potential amplitude seen during hypoxia is consistent with those of previous studies (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that cell hyperpolarization during hypoxia is not the result of G-protein-linked adenosine A1 receptors opening K+ channels. These results are in agreement with the studies of Leblond & Krnjevic (1989) who found that caffeine, a weak, non-selective adenosine antagonist (Bruns et al, 1986) did not attenuate hypoxia-induced hyperpolarization and Spuler & Grafe (1989) who found that pertussis toxin treatment (which abolished the hyperpolarization induced by application of exogenous adenosine) did not block the hyperpolarization during anoxia. The fall in evoked field potential amplitude seen during hypoxia is consistent with those of previous studies (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…The adenosine A, receptor is expressed at high levels in the cerebral cortex, hippocampus, and cerebellum (Mahan et al,199 1). Identical or closely related receptors are present postsynaptically, where they lower cyclic AMP, activate K+ channels, and/or inhibit Ca2+ channels (for review, see Stone,I99 l), and presynaptically, where they inhibit, via a pertussis toxin-sensitive guanine nucleotide binding protein (G protein) (Dolphin and Prestwich, 1985;Spuler and Grafe, 1989;Stone, 1991), the evoked release of a number of transmitters, including glutamate (Dolphin and Archer, 1983;Dolphin and Prestwich, 1985;Prestwich et al, 1987;Burke and Nadler, 1988;Dunwiddie et al, 1990;Poli et al, 1991), but notably excluding y-aminobutyric acid (GABA) (Yoon and Rothman,199 1).…”
mentioning
confidence: 99%
“…Indeed, Zhu & Krnjevic (1997) found that in CA1 pyramidal cells the hypoxic outward current was significantly reduced in the presence of 8‐SPT, a selective adenosine A1 receptor antagonist. On the other hand, the hyperpolarization induced by hypoxia or glucose deprivation was preserved in hippocampal slices in which the adenosine response was abolished by pretreatment with PTX (Spuler & Grafe 1989). Similarly, we observed no significant difference in the OGD‐induced outward current in controls versus cells treated with PTX or the adenosine receptor antagonist DPSPX.…”
Section: Discussionmentioning
confidence: 99%